2002
DOI: 10.1021/om020493b
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereoselective C−C Bond Formation between Alkynes:  Synthesis of Linear Dienynes from Alkynes

Abstract: Reactions of the iridacyclopentadienes (2a) and (2b) with RC⋮CH (R = C6H5, p-C6H4CH3) give linear conjugated dienynes (RC⋮CCHCHCHCH2 (3) and (5)) and benzene derivatives (RC6H5 (4) and RC6H3C6H8 (6, 6-aryl-1,2,3,4-tetrahydronaphthalene)). Linear conjugated dienynes 3 and 5 are exclusively obtained from the reactions of alkynyl iridacyclopentadienes (7) and (8) (R = C6H5 (a), p-C6H4CH3 (b), cyclohex-1-enyl (c)) with HOTf, respectively. The di- and trinuclear alkynyl iridacyclopentadienes (9a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…[76] + with two equivalents of acetylene and subsequent addition of an equivalent of a terminal arylacetylene, produced alkynyl iridacyclopentadienes such as 89 (Scheme 25). [77] Upon acidification with HBF 4 , 89 rearranged cleanly into iridacyclohexadiene 90, the product of a formal [2+2+1] alkyne cyclization.…”
Section: Iridabenzenes By [2+2+1] Cycloadditionmentioning
confidence: 99%
See 3 more Smart Citations
“…[76] + with two equivalents of acetylene and subsequent addition of an equivalent of a terminal arylacetylene, produced alkynyl iridacyclopentadienes such as 89 (Scheme 25). [77] Upon acidification with HBF 4 , 89 rearranged cleanly into iridacyclohexadiene 90, the product of a formal [2+2+1] alkyne cyclization.…”
Section: Iridabenzenes By [2+2+1] Cycloadditionmentioning
confidence: 99%
“…Although zwitterionic iridabenzene resonance structures such as 90' and 91' were invoked to help explain these types of rearrangements, metalla-aromatic species were not observed. [76] More recently though, Chin and Lee found that if MeCN is present during acidification of 90 with HBF 4 , cationic iridabenzene 93 is then isolated. Unique to 93 is its ability to reversibly react with weak Lewis bases such as CO and Et 3 N to form iridacyclohexadiene complexes 91 and 92, respectively.…”
Section: Iridabenzenes By [2+2+1] Cycloadditionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported coordination modes of the transition‐metal complexes of p ‐phenylenediethynide and its derivatives are presented in Scheme 2 (modes I, V, IX–XI). The mode that occurs most frequently is μ 1 ,μ 1 mode I, in which the terminal metal atoms can be palladium,33 iridium,34 platinum,35 gold,3a, 36 rhodium,37 or manganese38 in homometallic complexes, and also iron and rhenium in heterometallic complexes 39. The symmetrical μ 2 ,μ 2 mode V was reported recently by Lalinde and co‐workers through the reaction of [{Pt(PPh 3 ) 2 } 2 {μ‐η 2 :η 2 ‐(1,4‐HCC) 2 C 6 H 4 }] with cis ‐[PtR 2 S 2 ] complexes 40.…”
Section: Metal Complexes Of Isomeric Phenylenediethynides and The mentioning
confidence: 99%